'Did my grandfather storm the beaches of Normandy for this shit?' Mnemonic wars and digital games. (December 2022) - Tschiggerl, Martin
In the last 40 years, digital games have become an important negotiating space for experiencing historical worlds, and games with historical content enjoy an exceptionally high level of popularity. However, the way history is portrayed in these games has been the subject of heated controversy. These conflicts arise primarily around the question of what constitutes 'authentic' and thus 'correct' representations of the past and intensify when current ideological debates intersect with particularly emotionally charged collective memories. This article shows how collective memory can be contested when it becomes the object of ideological struggle.